DASH (Dietary Approaches to Stop Hypertension) Diet Principle-Based Snacks in Affecting Blood Pressure in Elderly - Retno Wahyu Ningsih; Joyeti Darni; Lalu Khairul Abdi (Poltekkes Kemenkes Mataram, 2022)
Background. Hypertension is a degenerative disease that is the leading cause of death globally. Handling hypertension can be done by giving the DASH diet. In this case, this study provides an interlude to the DASH diet. Research Methods. This study uses a quasi-experiment (pre-test-post-test control group design). The study subjects consisted of two groups: the treatment group with the administration of the DASH diet interlude and the control group. Research Result. Most of the subjects in this study were elderly 70-74 years (33.3%) in the treatment and 75-80 years (50%) in control. The research subjects were primarily female, with 27 elderly (75%). The mean blood pressure in both groups before the intervention was higher than the mean blood pressure after the intervention. The analysis of the two groups' different tests showed no difference in systolic and diastolic blood pressure before the intervention. However, there were differences in systolic and diastolic blood pressure after the intervention. Furthermore, giving a DASH diet interlude affected Systolic blood pressure (p=0.000) and Diastolic blood pressure (p=0.034) after the DASH diet snack was provided. Conclusion. There is an effect of giving the DASH diet interlude on blood pressure after giving the DASH diet snack.